Where mullein grows is where a portionless maid lives – phytonyms in the linguistic picture of the world painted by dialect users (in Kujawy region and apart from them): Gdzie rośnie dziewanna, tam bez posagu panna – miejsce fitonimów w językowym obrazie świata użytkowników gwar (na Kujawach i poza nimi) - Wierzbicka, Agnieszka (Rozprawy Komisji Językowej, 2019)
https://doi.org/10.26485/RKJ/2018/65/14 Article in Polish Most countrymen and countrywomen have always lived particularly close to nature. They obey the laws of nature, their life has been subordinated to the sequence of seasons and related chores, customs, rituals, and beliefs (both Christian and pagan). All of these practices find their reflection in language. The author attempts to depict the ways in which dialectl plant names function and how dialect users comprehend them as dialect phytonyms which carry the user’s subjective attitude to reality and reflect the conceptual and cognitive structures fixed in the collective consciousness.